Cancer induction and suppression with transcriptional control and epigenome editing technologies. Issue 2 (February 2018) - Nakade, Shota; Yamamoto, Takashi; Sakuma, Tetsushi
Abstract Cancer epigenetics is one of the most important research subjects in dissecting cancer mechanisms and therapeutic targets because the emergence and malignant transformation of various cancers are caused by unnatural expression of cancer-related genes attributed to their epigenetic errors. The original concept of cancer epigenetics basically stands on the analysis of the epigenetic status in naturally occurring cancer cells; however, the rapidly emerging technology called epigenome editing would change this situation drastically. Epigenome editing, the most promising derivative technology of genome editing, can modify the epigenetic states at the pre-defined genomic locus using the programmable effectors, consisting of various epigenetic factors combined with site-specific DNA-binding domains. This technology can be utilized in a reversible manner; i.e., cancer modeling can be achieved by introducing aberrant epigenetic marks in normal cells, and cancer suppression can be achieved by correcting the epigenetic errors in cancer cells. In this review, we summarize the basics of epigenome editing and cancer epigenetics, followed by the current examples of cancer induction and suppression with the transcriptional control and epigenome editing technologies.